Evidence of negative electrorefraction in type-II GaAs/GaAlAs short-period superlattice. (9th October 2015) - Shchukin, V A; Ledentsov, N N; Karachinsky, L Ya; Blokhin, S A; Novikov, I I; Egorov, A Yu; Maximov, M V; Gordeev, N Yu; Kulagina, M M; Ustinov, V M
Abstract: A type-II GaAs/GaAlAs short-period superlattice (SPSL) used as an electro-optic medium for the spectral range 820–850 nm is studied in a vertical microcavity geometry. SPSL is sandwiched between two GaAlAs distributed Bragg reflectors. Optical power reflectance (OR) spectra are measured as a function of applied reverse bias at different tilt angles and temperatures. All spectra reveal a blue shift of the reflectivity dip upon applied voltage which evidences a negative electrorefraction of the electro-optic medium. The shift enhances up to ∼0.6 nm once the exciton resonance is brought close to the wavelength of the reflectivity dip. As opposed to those modulators based on quantum–confined Stark effect, no increased absorption is observed at an applied bias, because the integrated intensity of the reflectivity dip in the OR spectra is virtually constant. This indicates a low absorption loss with applied bias and consequently a high potential for the increased dynamic range of the related modulator.